HUBUNGAN KETAHANAN PANGAN RUMAH TANGGA DENGAN STUNTING DI KECAMATAN MAULAFA, KOTA KUPANG. - Lero, Tisa Yulia Mila; Manek, Agustinus Hale; Rahmawati, Arfita (Jurnal Geografi, 2024)
The objectives of this study were: (I) To determine the condition of household food security with stunting in Maulafa Sub-district, Kupang City. (II) To determine the relationship between household food security and stunting in Maulafa Sub-district, Kupang City (III) To determine the distribution pattern of stunting based on household food security in Maulafa Sub-district, Kupang City. This type of research is quantitative research. The subjects in this study amounted to 100 toddlers consisting of 50 stunted toddlers and 50 non-stunted toddlers. Data analysis techniques used are validity test, reliability test, univariate test, bivariate test with the help of spss and nearest neighbor analysis for distribution patterns with the help of ArcGis 10.2 software. The results of the calculation of the distribution pattern of household food security with stunting in Maulafa District are clustered, this shows that the distance between one location and another tends to cluster in a certain area. The bivariate test results show that the p-value significance value is 0.000 which is smaller than 0.05. Based on the results of the analysis, it is concluded that there is a significant relationship between household food security and the incidence of stunting. The results of the test of the relationship between household food security and the incidence of stunting - 0.466 which is in a moderate correlation with a negative relationship. So it can be interpreted that the higher the household food security, the lower the incidence of stunting.